Clinical relevance of herpes simplex virus viremia in Intensive Care Unit patients. Issue 1 (July 2015) - Lepiller, Q.; Sueur, C.; Solis, M.; Barth, H.; Glady, L.; Lefebvre, F.; Fafi-Kremer, S.; Schneider, F.; Stoll-Keller, F.
Summary Objectives To determine the clinical relevance of herpes simplex virus (HSV) viremia episodes in critically ill adult patients. Methods 1556 blood samples obtained for HSV PCR analysis in Intensive Care Unit (ICU) patients over 4 years were retrospectively analyzed, focusing on the comprehensive analysis of 88 HSV-viremic patients. Results HSV DNA was detected in 11.8% of samples from the ICU. HSV viral loads remained below 5 × 102 copies/ml in 68.2% of patients and exceeded 104 copies/ml in 7.9%. Episodes of HSV-viremia correlated with immunosuppressed status and mechanical ventilation in 79.5% and 65.9% of patients, respectively. Only a subset of patients exhibited HSV-related organ damage, including pneumonia and hepatitis (10.2% and 2.3%, respectively). The mortality rate in HSV-viremic patients was not significantly increased compared to the overall mortality rate in the ICU (27.3% vs. 22.9%, p = 0.33). Only patients with high HSV viral loads tended to have a higher, though non-significant, death rate (57.1%, p = 0.14). Conclusions Our results suggest HSV viremia is common in ICU patients, potentially favored by immunocompromised status and mechanical ventilation. The global impact of HSV-viremia on mortality in the ICU was low. Quantifying HSV DNA may help identifying patients at-risk of severe HSV-induced symptoms.